SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169171-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interfacial Tensions and Contact Angles of Surfactant-in-Brine/Oil/Shale Systems: Implications to Enhanced Oil Recovery in Shale Oil Reservoirs

Abstract: Unconventional shale oil resources have emerged as a significant source of fossil fuels in recent years. The oil contained in shales is held in natural microfractures, micropores, and inside nanopores of the organic matter. The strong capillary forces in these pores can bind the oil to the surface with strengths that are inversely proportional to the pore radius. In order to recover more oil from these pores, it is beneficial to reduce the capillary pressure by manipulating the interfacial tension and contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The literature on shale oil rocks indicates that they are most likely oil-wet (Phillips et al, 2007;Wang et al, 2011;Mirchi et al, 2014). Shuler et al (2011) did some surfactant spontaneous imbibition tests.…”
Section: [11]surfactant Eor In Shale Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on shale oil rocks indicates that they are most likely oil-wet (Phillips et al, 2007;Wang et al, 2011;Mirchi et al, 2014). Shuler et al (2011) did some surfactant spontaneous imbibition tests.…”
Section: [11]surfactant Eor In Shale Reservoirsmentioning
confidence: 99%
“…Takahashi and Kovscek (2010) studied the wettability of a low-permeability siliceous shale at different pH values and found that the shale samples became more water-wet at very low or very high pH. Mirchi et al (2014) observed that adding surfactants in brine reduced the interfacial tension between brine and oil and increased the dynamic contact angle of oil drops (became more water-wet).…”
Section: [11]surfactant Eor In Shale Reservoirsmentioning
confidence: 99%
“…Surfactants are amphiphilic organic chemicals comprising hydrophobic and hydrophilic compounds. When injected into ultra-low permeability hydrocarbons rocks, they reduce the oil viscosity, pore capillary forces and the interfacial tension between water and oil and decrease oil-wet wettability [7][8][9].…”
Section: Surfactant Treatment/floodingmentioning
confidence: 99%
“…[] investigated the wettability of organic shale samples and concluded that the samples are strongly oil‐wet in the presence of air. They further mentioned that deionized (DI) water causes the highest contact angle on the sample surface and that highly saline solutions lead to the lowest contact angle whereas another study [ Mirchi et al ., ] suggests that the contact angle increases with salinity. Furthermore, the amount of water uptake by spontaneous capillary imbibition was calculated using an analytical solution [ Birdsell et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that organic shales will have mixed hydrocarbon‐water wet surfaces in both organic and inorganic pores and thus the bulk wettability is defined by the phase dominating the wetting behavior. This is why the contact angles of organic‐rich shales vary significantly with different ionic strength solutions on different samples [ Engelder et al ., ; Mirchi et al ., ; Roshan et al ., ; Xu and Dehghanpour , ]. It should therefore be noted that parameters such as pressure, temperature, and ionic strength can significantly contribute to variations in contact angle e.g., when a fracturing fluid invades the organic shale matrix, the rock wettability can alter because of change in pressure and temperature or the reaction of clay minerals with the ions in the injected solution in the invaded zone.…”
Section: Introductionmentioning
confidence: 99%